Cognitive function in hypothyroid patients: a tertiary care-based cross-sectional study - Jamatia, S. N. Naithok; Debbarma, Aghore; Debbarma, Mahendra; Debbarma, Pranab; Debbarma, Tanusri; Singnarpi, Evalyn; Debbarma, Bikash (International Journal of Research in Medical Sciences, 2024)
Background: Estimation of cognitive impairment among hypothyroid individuals plays an important role in intervening in the disease progress at the earliest. The present study was conducted to measure the cognitive impairment in a hypothyroid state. Methods: A cross-sectional study was conducted among 260 sample of hypothyroid patients at Agartala Government Medical College Hospital from January to June 2024 using a case record form where pregnant state, acute illnesses, and co-morbidities were excluded. The General Practitioner Assessment of Cognition scale was used to measure the cognitive impairment. Both descriptive and inferential statistics were used using SPSS vs 21.0. Results: Out of 260 cases of hypothyroidism, 32.7% have cognitive impairment. Only 16.9% of the subjects with sub-clinical states showed cognitive impairment but 58% of them with visible clinical manifestations showed cognitive impairment (p-value .001). The cognitive function was more impaired among males (51.8%) than females (28.0%) which is found to be statistically significant (p-value .004). Conclusions: The study concluded that every third person had cognitive impairment among hypothyroid patients. Clinical hypothyroidism, advance age, and males were associated with cognitive impairment. Newly diagnosed cases were found to show increased impairment.